Influence of sport climbing on selected physical abilities and heart rate - Cerná, L.; Cerný, P.; Lhotová, Z.; Kabešová, H. (Journal of Outdoor Activities, 2017)
The goal of the research is to find out the influence of 11-week long intervention program of sports climbing on the chosen physical abilities and values of maximal heart rate. The research group was made up by adults (n=22) in age 26,4 years (±9,9). The improvement was proven in tests of upper limbs muscle strength, flexibility and coordination. We did not register significant changes in the values of maximal heart rate while climbing. For the improvement of muscle ability is this intervention sufficient. If the goal of intervention is improvement of climbing performance then the range of the intervention must be bigger.